2024
DOI: 10.5603/pjnns.97343
|View full text |Cite
|
Sign up to set email alerts
|

Normal pressure hydrocephalus, or Hakim syndrome: review and update

Philip W. Tipton,
Benjamin D. Elder,
Petrice M. Cogswell
et al.

Abstract: This review makes the case that idiopathic normal pressure hydrocephalus (iNPH) is an outdated term because new information indicates that the syndrome is less idiopathic and that the cerebrospinal fluid (CSF) pressure of normal individuals is affected by several factors such as body mass index, age, and sex. Our review updates the epidemiology of iNPH and provides a clinical approach to the management of these patients. All the clinical features of iNPH are common in older individuals, and each has many cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…The exact cause of idiopathic NPH is not known. At the Hydrocephalus 2023 congress, many experts suggested that the terminology of NPH should be revised to match our evolving physiological knowledge [33]. At present, there is no consensus on the aetiology of impairments in CSF pulsatility [12,19,25,32].…”
Section: Impact Of Shunt Placement On Intraventricular Csf Dynamicsmentioning
confidence: 99%
“…The exact cause of idiopathic NPH is not known. At the Hydrocephalus 2023 congress, many experts suggested that the terminology of NPH should be revised to match our evolving physiological knowledge [33]. At present, there is no consensus on the aetiology of impairments in CSF pulsatility [12,19,25,32].…”
Section: Impact Of Shunt Placement On Intraventricular Csf Dynamicsmentioning
confidence: 99%